The Lakes and Rivers Mentioned in the Inscriptions of Kok Turks - Saadettin, Gomes (Historia Mongolarum, 2010)
As it is known, when the history is defined, the place clement must also be considered. For this reason, historians focus not only on time but also on place and social results while they are talking about past events. The written sources in the language Kuk Tьrks are the most precious Works of our history of Central Asia where a-thousands-year old Turkish history took place and still Turks live there. One can run across these Works in a wide area, beginning from China on the cast, to the middle and North Europe on the west. Although there been thousands of rivers and lakes over the elder furkish land. In this study, it was tried to find out the original place of the lakes and rivers that are mentioned at the inscriptions of the Kuk Türk and Uygur period and their historical importance was taken into consideration in a short manner. For this reason an alphabetical order has been followed up.